2015
DOI: 10.5152/jtgga.2015.15128
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy versus laparotomy for the management of endometrial carcinoma in morbidly obese patients: a prospective study

Abstract: Results: Postoperative complications were significantly higher in the laparotomy group. Hospital stay in the laparoscopy group was significantly lower than that in the laparotomy group. The visual pain scores were significantly higher in the laparotomy group on the first, second, and third postoperative days and on the day of discharge from the hospital. Resuming activity took a significantly longer time in the laparotomy group (34.70 days) than in the laparoscopic group (17.89 days). Conclusion:With the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Следует подчеркнуть, что большинство авторов значительное внимание уделяют опыту хирурга и техническому оснащению операционной [18]. Продол-жительность операции, кровопотеря, осложнения, проа-нализированные в исследовании, сопоставимы с данными мировой литературы [4]. В проведенном исследовании в 34,3% случаев при началь-ном раке эндометрия операция являлась лишь первым этапом комбинированного противоопухолевого лечения.…”
Section: Discussionunclassified
“…Следует подчеркнуть, что большинство авторов значительное внимание уделяют опыту хирурга и техническому оснащению операционной [18]. Продол-жительность операции, кровопотеря, осложнения, проа-нализированные в исследовании, сопоставимы с данными мировой литературы [4]. В проведенном исследовании в 34,3% случаев при началь-ном раке эндометрия операция являлась лишь первым этапом комбинированного противоопухолевого лечения.…”
Section: Discussionunclassified
“…Obesity-related risks appear to have significantly reduced with the introduction of laparoscopy, especially for procedures popularly known as providers of postoperative complications in the obese [ 18 20 , 41 44 ]. Nonetheless, the association between obesity and adverse surgical outcome may not be clear-cut as contradictory reports are available [ 7 , 32 , 40 , 45 ].…”
Section: Main Textmentioning
confidence: 99%
“…This association is confirmed by some of the rare available reports in Africa [ 8 , 14 – 17 ]. With the introduction of laparoscopic surgery, surgical interventions appear to have become much safer in persons with excess weight [ 18 20 ]. Notwithstanding the above mentioned, some authors have reported contrary findings on the role of obesity and overweight in predicting surgical morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…When all these conditions are fulfilled the rate of success of laparoscopic management is pretty high even in morbidly obese patients. [25] For surgeons, the main problem is the correct visualization of the operative field. The ports may sometimes be placed higher on the abdomen, above the umbilicus, especially for the optique.…”
Section: Epidemiological Datamentioning
confidence: 99%